Smokers' awareness of filter ventilation, and how they believe it affects them: findings from the ITC Four Country Survey. Issue 1 (15th June 2021) - King, Bill; Borland, Ron; Le Grande, Michael; O'Connor, Richard; Fong, Geoffrey; McNeill, Ann; Hatsukami, Dorothy; Cummings, Michael
Abstract : Background: Filter ventilation creates sensations of 'lightness' or 'smoothness' and is also highly effective for controlling machine-tested yields of tar, nicotine and carbon monoxide. Nearly all factory-made cigarettes (FMC) now have filter ventilation in countries such as Australia, Canada, the UK and the USA. Research conducted before 'light' and 'mild' labelling was banned found low smoker awareness of filter ventilation and its effects. This study explores current levels of awareness of filter ventilation and current understanding of its effects in these four countries. Methods: We used data from the 2018 wave of the ITC Four Country Smoking and Vaping Survey with samples from USA, England, Canada and Australia. Analyses were conducted initially on a weighted sample of 11 844, and subsequently on 7541 daily FMC smokers. Findings: Only 40.3% of all respondents reported being aware of filter ventilation. Among daily FMC smokers, only 9.4% believed their cigarettes had filter ventilation. Believing that their usual cigarettes are smoother was positively associated with believing they are also less harmful. Both these beliefs independently predict believing their cigarettes are ventilated (smoother OR=1.97 (95% CI 1.50 to 2.59) and less harmful OR=2.41 (95% CI 1.66 to 3.49) in relation to those believing each characteristic is average. Interpretation: Awareness of filter ventilation is currently low, despite decades of public 'education efforts around the misleading nature of 'light' and 'mild" descriptors. Few smokers realise that their cigarettes almost certainly are vented. Smokers who believed their cigarettes have filter ventilation were more likely to believe they were both smoother and less harmful. Awareness of the technology appears to be insufficient to prevent smokers being deceived by it. Filter ventilation is inherently misleading to smokers and it is time to ban it.